Effects of Oil and Sediment Properties and Mixing States on the Formation and Settling of Oil‐Particle Aggregates. Issue 2 (15th February 2022) - Yu, Yue; Xiong, Deqi; Qi, Zhixin; Li, Wenxin; Sun, Ruiyang; Fu, Sinan
Abstract: Understanding the interaction of oil droplets with suspended particulate matter is important not only for sunken oil modeling but also for emergency response. In this study, the effects of mixing time and energy, oil type, and sediment concentration and size on the oil content, morphology, and density of oil‐particle aggregates (OPAs) were investigated through a series of wave tank experiments and sedimentation tests. The results showed that loads of oil and particles in OPAs are high under high mixing energy. Under turbulent hydrodynamics, moderately viscous oils form OPAs more easily and sink rapidly to the seabed. Moreover, an increase in the density and oil capacity of OPAs is observed at a higher sediment concentration. More oil is captured by finer sediments. However, the corresponding oil‐sediment aggregates generally show lower density compared with those formed by larger sediments. The oil‐seawater interfacial tension ( IFT ow ) diminishes with the addition of sediments, further promoting oil dispersion. The increasing duration and mixing energy produce more flake OPAs and multiple‐droplet OPAs. Oil droplets tend to be surrounded by several small particles but attach to the surface of large particles. Regardless of oil type and sediment concentration, the structure of OPAs does not change significantly. Plain Language Summary: In this study, quantitative data regarding the formation of dispersed oil and oil‐particle aggregates (OPAs) in a small wave tank were measured to overcome the effect of excessive mixing energy in previous batch experiments. A series of sedimentation tests were conducted to understand how sediment particles influence the accumulation of petroleum by forming different aggregation structures with settling velocities. The results of this study can be used to better understand the transport and fate of spilled heavy oils in the Bohai Sea and improve oil spill response. Key Points: Oil‐particle adhesion is significantly inhibited and the density of oil‐particle aggregates is relatively low under weak mixing energy Oil‐particle aggregates formed with larger sediment have less trapped oil but settle faster Increase of the duration and mixing energy results in more flake oil‐particle aggregates and multiple‐droplet oil‐particle aggregates